ORIGIN, TREATMENT AND PREVENTION OF THROMBOPHILIA DISEASE - Umurzaqova Raxilaxon Zakirovna (Scholar Express Journals, 2022)
Thrombophilia refers to a group of conditions where the blood clots more easily than normal. This can lead to unwanted blood clots (called thromboses) forming within blood vessels. These blood clots can cause problems such as deep vein thrombosis (DVT) or pulmonary embolism. See the separate leaflets called Deep Vein Thrombosis and Pulmonary Embolism for more details.
Keywords: Thrombophilia; called platelets; thromboses